First-Principles Design of Refractory High Entropy Alloy VMoNbTaW - Shumin Zheng; Shaoqing Wang (Entropy, 2018)
The elastic properties of seventy different compositions were calculated to optimize the composition of a V⁻Mo⁻Nb⁻Ta⁻W system. A new model called maximum entropy approach (MaxEnt) was adopted. The influence of each element was discussed. Molybdenum (Mo) and tungsten (W) are key elements for the maintenance of elastic properties. The V⁻Mo⁻Nb⁻Ta⁻W system has relatively high values of C44, bulk modulus (B), shear modulus (G), and Young’s modulus (E), with high concentrations of Mo + W. Element W is brittle and has high density. Thus, low-density Mo can substitute part of W. Vanadium (V) has low density and plays an important role in decreasing the brittleness of the V⁻Mo⁻Nb⁻Ta⁻W system. Niobium (Nb) and tantalum (Ta) have relatively small influence on elastic properties. Furthermore, the calculated results can be used as a general guidance for the selection of a V⁻Mo⁻Nb⁻Ta⁻W system.